1989
DOI: 10.1002/maco.19890400403
|View full text |Cite
|
Sign up to set email alerts
|

The influence of manganese on the High‐temperature oxidation of iron‐chromium alloys

Abstract: An investigation has been undertaken into the oxidation behaviour of manganese-containing Fe-28% Cr alloys in oxygen at 800" and 1OOO"C. The presence of the tertiary element has a detrimental effect on the oxidation resistance, resulting in enhanced scale-growth rates during isothermal exposure and increased incidences of scale failure at temperature. This is largely due to relatively rapid rates of diffusion of manganese across the Cr203 scale and formation of MnCrzOd spinel on its outer surface. The scale on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(47 citation statements)
references
References 31 publications
3
43
0
1
Order By: Relevance
“…Cr 2 O 3 has a corundum structure, which consists of an hcp array of oxygen with two-thirds of the octahedral sites occupied by the metal [26][27][28]. µm.…”
Section: Microstructures Of the Cr-rich Oxide Scalementioning
confidence: 99%
“…Cr 2 O 3 has a corundum structure, which consists of an hcp array of oxygen with two-thirds of the octahedral sites occupied by the metal [26][27][28]. µm.…”
Section: Microstructures Of the Cr-rich Oxide Scalementioning
confidence: 99%
“…Based on the results it can be suggested that the formation of larger voids underneath the oxide scale in Ti rich Ni-based alloys is invoked not only by process described by researchers [13,14,1415] but can be enhanced further by oxygen vacancies existing in the TiO 2 phase that formed here, however, for analytical instruments used in this study it was unreachable.…”
Section: Voids Formationmentioning
confidence: 72%
“…Another mechanism for voids formation have been described by Stott at al. [14], and Juana at al. [15] suggesting that the phenomena is related strictly to the breaking mechanism of the oxide scale in pure steam at 700°C.…”
Section: Voids Formationmentioning
confidence: 94%
See 1 more Smart Citation
“…Este resultado mostra que a liga estudada possui baixa resistência à oxidação em 800°C quando comparada com os dados reportados na literatura para o comumente utilizado 304 oxidado na mesma temperatura por até 100 h (cerca de 0,23 mg/cm 2 ) (ISSARTEL et al, 2004). Entretanto, deve ser mencionado que o aço 304 possui elevado teor de Cr e baixo teor de Mn que são elementos que influenciam significativamente na resistência à oxidação em elevada temperatura (STOTT, et al, 1989). A Figura 3 (b) mostra o quadrado do ganho de massa da liga estudada, onde é possível observar um incremento linear com o tempo de oxidação, indicando que o comportamento de oxidação dos materiais estudados obedece à lei parabólica.…”
Section: Resultsunclassified